Association of a body fluid with a DNA profile by targeted RNA/DNA deep sequencing. (December 2017) - Ingold, S.; Haas, C.; Dørum, G.; Hanson, E.; Ballantyne, J.
Abstract: Our goal for this study was, in addition to body fluid/tissue identification, to associate tissue specific mRNA transcripts to the donor of a stain. This is especially interesting for mixed body fluid samples, where we can find out who contributed which body fluid. Within the tissue specific sequences we looked for coding region variants (cSNPs) that discriminate European individuals the most. We successfully tested a targeted MPS assay for the Illumina MiSeq platform in 188 European individuals for the detection of the 35 selected cSNPs on gDNA level. The match probabilities for the SNPs within one body fluid and for sets of markers from different body fluids confirmed the discriminatory power of these markers. A separate targeted cSNP panel on RNA level showed good specificity for blood, semen and menstrual blood. For saliva, vaginal secretion and skin, the marker design needs to be optimized with special attention to cross reactivity with DNA contaminants. As a proof-of-principle we could demonstrate that with our targeted DNA and RNA MPS assays we are able to assign a body fluid to a specific individual.